Antiplatelet drug resistance in patients with coronary heart disease - V. A. Sulimov; E. V. Moroz (Кардиоваскулярная терапия и профилактика)
Coronary angioplasty is an important component of coronary heart disease (CHD) management. There is a substantial evidence of the need for dual antiaggregant therapy (clopidogrel and aspirin) in this clinical group, both before and after the intervention. The development of thrombotic complications during antiaggregant therapy suggests the antiplatelet drug resistance. The prevalence of this condition varies from 5% to 45% for aspirin, and from 20% to 45% for clopidogrel, depending on the assessment method and the specific clinical group. For dual antiplatelet therapy, the resistance prevalence is 6-8%. Presently, the gold standard method of the platelet functional activity assessment is optical aggregometry. To assess the resistance to aspirin, arachidonic acid is used as an aggregation inductor, with the calculation of absolute aggregation levels. To assess the resistance to clopidogrel, ADP is used as an aggregation inductor, and the relative aggregation parameters are calculated. The development of aspirin resistance is influenced by biological, clinical, and genetic factors. The clopidogrel resistance is associated with certain medications, hyperglycemia, atherosclerosis, and CYP2C19*2 gene polymorphism. Identification of the patients resistant to antiplatelet drugs enables the clinicians to adjust the antiplatelet treatment reasonably early and to reduce the risk of cardiovascular events. The possible methods of overcoming antiplatelet drug resistance are to double the loading and maintenance doses of clopidogrel and to use new agents.